Dental anomalies in Dromiciops gliroides (Microbiotheria, Microbiotheriidae), Caenolestes fuliginosus and Rhyncholestes raphanurus (Paucituberculata, Caenolestidae) - Martin, Gabriel Mario (2007)
Dental anomalies are described after analyzing series of skulls and mandibles of three species of South American marsupials: the monito del monte (Dromiciops gliroides), the silky shrew-opossum (Caenolestes fuliginosus) and the Chilean shrew-opossum (Rhyncholestes raphanurus). The anomalies are classified into three categories: (1) supernumerary or missing teeth in normal positions of the dental series, (2) morphological anomalies like teeth fusion or anomalous crown shape, and (3) presence of teeth in unusual positions. Cusp fusion and supernumerary teeth at the end of the toothrow have been observed predominantly in D. gliroides. A tendency to find supernumerary or missing teeth is observed between the procumbent incisors and the second lower premolars in caenolestids. Possible causes for these anomalies and their morphofunctional value are discussed. A comparison with other marsupials is presented and discussed. Isolation of local populations and its effects on genetic drift processes might explain the high percentage of dental anomalies.